An Analysis on Students’ Listening Comprehension Problems at the Third Semester English Language Education of Universitas Islam Riau - Erza Muhammad Ikhsan; Syofianis Ismail (DISCOVERY JOURNAL, 2022)
This study discussed about Difficulties Faced by Third Semester Students toward Listening Comprehension. The aim of the study were to find out the problems most encountered by students from three major problems, there are Quality of Listening material, Unfamiliar Vocabulary, Length and Speed of Listening. The research was conducted in State Islamic University of Riau. Descriptive method was used to analyze and to find the result about the problems. The population of this study was third semester students of English Language Education Department of teacher training and education faculty Academic year 2019/2020. The number of population was 98 students from two classes. Total sampling technique was used to select all students as the subject in this study. Data was gathered by questionnaire and interview was used to confirm students’ answer. The data showed that the quality of recorded material was problem faced by most students. The conclusion is Quality of recorded material was the main problem that most frequently encountered by students, followed by unfamiliar vocabulary, length and speed of listening. Knowing about students’ major problems can motivate and help the lecturers to develop effective learning strategies for the students to improve their listening abilities. It provided solutions also to overcome the problems were: the teacher should adapt and improve listening material, activate students’ vocabulary, give some strategies in listening and always motivate students. The results of the study may also be useful for those who are interested in this study.